Is it ESG for a better world? / Dr. Muhammad Hariz Hamid, Dr. Mohd Faizal Jamaludin and Dr. Muslimah Mohd Jamil - Hamid, Muhammad Hariz; Jamaludin, Mohd Faizal; Mohd Jamil, Muslimah (Universiti Teknologi MARA, Kedah, 2024)
ESG, which stands for Environmental, Social, and Governance, is critical in modern investing. It involves assessing a company's impact on the environment (E), its relationships with employees and communities (S), and its leadership and ethics (G). The measures, which are known as ESG metrics, serve as essential tools that help investors make informed decisions aligned with their values and principles. Investing in ESG-focused companies offers greater resilience to risks, long-term sustainability, and reduced market volatility.